1988
DOI: 10.4141/cjss88-048
|View full text |Cite
|
Sign up to set email alerts
|

Allocation and Microbial Utilization of C in Two Soils Cropped to Barley

Abstract: C in two soils cropped to barley. Can. J. Soil This study was undertaken to compare some aspects of carbon cycling in a Gray Luvisol at Breton and a Black soil at Ellerslie, Alberta cropped to barley. Comparisons of the above and below-ground allocation of carbon, distribution of carbon in soil, and microbial use of carbon were made between sites. Shoot C. root C, microbial biomass C, soil organic C, water soluble organic C, and polysaccharide C were measured on four dates between 31 July and 20 Oct. 1986. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Statistical analysis was conducted for ANOVA (P3V), multiregression (P2R) and principal component analyses (P2R) on NH + 4 , NO − 3 in soils before fumigation and soils fumigated and nonfumigated after 10 days incubation using BMDP statistical software (Dixon, 1983). Three crops together with summer fallow were categorized as treatment whereas four sampling dates were considered as another treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Statistical analysis was conducted for ANOVA (P3V), multiregression (P2R) and principal component analyses (P2R) on NH + 4 , NO − 3 in soils before fumigation and soils fumigated and nonfumigated after 10 days incubation using BMDP statistical software (Dixon, 1983). Three crops together with summer fallow were categorized as treatment whereas four sampling dates were considered as another treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lynch and Panting (1980a) had observed that correlation exist between soil microbial biomass and root growth and rooting density of the crop. Foster and Rovira (1976) found that older roots of wheat at the flowering stage showed consistent development of microorganisms both in the rhizosphere and in the outer cortical cells and cell walls.…”
Section: Soil Microbial Biomass C and Respirationmentioning
confidence: 96%
See 2 more Smart Citations
“…Soluble C was not measured in the laboratory incubation; however, the initial pool size was estimated from previous work on similar soils (Dinwoodie and Juma 1988 The active C and N pools represent rapid cycling insoluble organic matter pools, consisting of microbial metabolic products and recently stabilized materials (Paul and Juma 1981). Campbell and Souster (1982) half-life of > 600 yr (Campbell et al 1967 Rate of bacterial CO2-C evolution (Rb) (pg C g-l soil d-l) was calculated using growth and maintenance components (Hunt et al 1984 the active C pool (Hunt et al 1984).…”
mentioning
confidence: 99%